if (y-p) is a factor of the polynomial p⁶-py⁵+y⁴-py³ + 3y -p-2. then the value of p is :

# if (y-p) is a factor of the polynomial p⁶-py⁵+y⁴-py³ + 3y -p-2. then the value of p is :

### 2 thoughts on “if (y-p) is a factor of the polynomial p⁶-py⁵+y⁴-py³ + 3y -p-2. then the value of p is :<br />”

### Leave a Comment

You must be logged in to post a comment.

9322664561 per muje gali do to me tome free fire ke id me topup duga

Step-by-step explanation:y-p=0

y=p

p6-pxp5 +p⁴-pxp³+3xp-p-2=0

p6-p6+p⁴-p⁴+3p-p-2=

2p-2=0

2p=2

p=1 PLEASE MAKE ME BRILLIANT